Crowdfunding and intellectual property rights : a case study of Malaysia - Lau, Keng Liang (2018)
Crowdfunding is a novel method for funding a variety of new ventures. It allowing creators of for-profit, cultural, or social projects to request funding from many individuals, often in return for souvenirs, access to future products or equity. It has become the alternative way for many entrepreneurs and inventors (project owner) to raise fund for their businesses. However, the public nature of the online crowdfunding raises many issues including intellectual property issues that relevant to the project owners. Moreover, intellectual property issues and crowdfunding have not been well developed especially in the Malaysian context. Thus, this study aims to explore what are the intellectual property issues related to crowdfunding practice especially the reward-based crowdfunding practices in Malaysia. For that purpose, this study used qualitative methods through in-depth interview with six respondents from Malaysian crowdfunding platforms and crowdfunding project owners. They were chosen because they are the experts who directly involved in Malaysian crowdfunding industry and they have experiences in dealing with the intellectual property issues of crowdfunding practices in Malaysia. The finding of this study suggested that there are intellectual property issues related to crowdfunding namely: patent protection, patent infringement allegation and breach of confidentiality. This study is hoped to provide a clear understanding and knowledge for academicians and public in Malaysia regarding the reward crowdfunding’s process and intellectual property rights. This could benefit project owners in implementing crowdfunding campaign in Malaysia. Moreover, this research also advocates some useful recommendations for project owners on how to make a successful crowdfunding campaign. Consequently, a more detailed picture about potential intellectual property issues in crowdfunding was highlighted in this research. It was also found that the importance of intellectual property protection and crowdfunding is still less encouraging amongst the users of crowdfunding. The finding also suggested that although the development of intellectual property rights and crowdfunding is still at the age of infancy, there is a direction and possibility of its importance for the future especially in Malaysia. Crowdfunding users should be more aware of the importance of intellectual property rights before they launch their crowdfunding campaign through online basis.